The impact of ChatGPT on part-time translators working with the English language: a threat or a complementary tool? - Zhou, Lina; Abdullah, Muhammad Alif Redzuan; Syed Abdullah, Syed Nurulakla; Peng, Junhua (Sciedu Press, 2025)
Since its launch on November 30, 2022, the artificial intelligence (AI) language model ChatGPT has garnered immense attention and experienced exponential growth in popularity. As one of the largest and most sophisticated models in the market, ChatGPT presents both challenges and opportunities for part-time translators, especially those working primarily with the English language. However, there exists a pervasive perception that part-time translators may face unemployment due to AI advancements. This study examines the attitudes of part-time translators toward the fear that ChatGPT will replace them and explores strategies for adapting to the AI-driven environment. Using an empirical sociological approach with mixed methods, this research finds that part-time translators view ChatGPT as a tool that can augment their capabilities and enhance job efficiency when translating into or from English. The findings suggest that AI can serve as a complement rather than a replacement, providing valuable support for less creative or repetitive translation tasks. This study provides a foundation for future research on the impact of AI on vulnerable occupations within the English language sector.